ADVANCEMENTS IN GREEN CHEMISTRY: OPTIMIZING SUSTAINABLE SYNTHESIS PATHWAYS FOR BIODEGRADABLE POLYMERS FROM AGRICULTURAL WASTE MATERIALS - Suwahono Suwahono; Nong Chai; Jari Koskinen (Yayasan Adra Karima Hubbi, 2026)
Growing environmental concerns regarding plastic pollution, fossil resource depletion, and greenhouse gas emissions have intensified efforts to develop sustainable alternatives to petroleum-based polymers. Agricultural waste provides biomass containing cellulose, hemicellulose, starch, and lignin that can be transformed into biodegradable polymers through responsible synthesis pathways. Green chemistry offers a framework for reducing hazardous chemicals, energy consumption, and resource inefficiency while supporting circular bioeconomy principles. This study evaluated green chemistry strategies for producing biodegradable polymers from agricultural waste while enhancing polymer performance, sustainability, and industrial feasibility. A mixed-methods sequential explanatory design involved 480 biomass samples and 210 laboratory- and pilot-scale synthesis experiments representing conventional, optimized, and sustainable production pathways. Quantitative data were analyzed using descriptive statistics, structural equation modeling, hierarchical regression, mediation, and moderation analyses. Qualitative evidence from expert interviews, industrial observations, lifecycle assessments, and policy documents was examined thematically. Findings showed that integrated green chemistry improved biomass conversion efficiency, polymer yield, molecular stability, biodegradation, catalyst recovery, energy efficiency, and lifecycle sustainability. Catalyst recovery partially mediated the relationship between green chemistry implementation and environmental performance, while reaction optimization strengthened the effect of biomass conversion on polymer quality. Sustainable production therefore requires coordinated biomass use, catalyst innovation, process optimization, and circular economy strategies.